2018
DOI: 10.1016/j.tranon.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Synergistic Chemoimmunotherapy for Head and Neck Cancer Using Peritumoral Immature Dendritic Cell Injections and Low-Dose Chemotherapies

Abstract: The lack of available tumor antigens with strong immunogenicity, human leukocyte antigen restriction, and immunosuppression via regulatory T-cells (Tregs) and myeloid-derived suppressor cells are limitations for dendritic cell (DC)–based immunotherapy in patients with advanced head and neck cancer (HNC). We sought to overcome these limitations and induce effective antitumor immunity in the host. The effect of low-dose docetaxel (DTX) treatment on DC maturation was examined in an ex vivo study, and a phase I cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…In addition, several preclinical trials have shown that docetaxel also enhances CD8 + T-cell responses and antitumor activity [27,28], although our results showed that the frequency of CD8 + TILs and CD103 + cells in the sub-group that received PC was not decreased signi cantly than that in the non-PC sub-population. Brie y, PC may be the main reason for the transformation of the T-cell landscape, as substantiated previously [29,30]. with the smoking history of the patients with HNSCC.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, several preclinical trials have shown that docetaxel also enhances CD8 + T-cell responses and antitumor activity [27,28], although our results showed that the frequency of CD8 + TILs and CD103 + cells in the sub-group that received PC was not decreased signi cantly than that in the non-PC sub-population. Brie y, PC may be the main reason for the transformation of the T-cell landscape, as substantiated previously [29,30]. with the smoking history of the patients with HNSCC.…”
Section: Discussionsupporting
confidence: 54%
“…35 Previously, DTX has been shown to enhance antitumor T cell responses against lung cancer by eliciting immunogenic cell death (ICD). 36 We examined whether the tumor regression caused by DTX-sHDL-CpG treatment (Figure 5B–C) was due to the release of danger signals ( e.g., CRT and HMGB1) associated with ICD. Briefly, mice bearing GL26 tumors harboring a surrogate tumor antigen, ovalbumin (OVA), were treated with saline or DTX-sHDL-CpG nanodiscs at the indicated doses and schedule (Figure 6A); mice were euthanized one day after the end of the treatment and brains were processed for flow cytometry analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxic T lymphocytes are crucial for mediating tumor-specific adaptive immunity; however, their activity is suppressed in the presence of GBM . Previously, DTX has been shown to enhance antitumor T cell responses against lung cancer by eliciting immunogenic cell death (ICD) . We examined whether the tumor regression caused by DTX-sHDL-CpG treatment (Figure B,C) was due to the release of danger signals ( e.g ., CRT and HMGB1) associated with ICD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations